2023
DOI: 10.3390/ijms24021007
|View full text |Cite
|
Sign up to set email alerts
|

Sperm DNA Fragmentation and Sperm-Borne miRNAs: Molecular Biomarkers of Embryo Development?

Abstract: The evaluation of morpho-functional sperm characteristics alone is not enough to explain infertility or to predict the outcome of Assisted Reproductive Technologies (ART): more sensitive diagnostic tools are needed in clinical practice. The aim of the present study was to analyze Sperm DNA Fragmentation (SDF) and sperm-borne miR-34c-5p and miR-449b-5p levels in men of couples undergoing ART, in order to investigate any correlations with fertilization rate, embryo quality and development. Male partners (n = 106… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 57 publications
(79 reference statements)
0
8
0
Order By: Relevance
“…Similarly, Shi et al, (2020) observed a negative correlation between spermatogenic miR-34c levels and embryo developmental kinetics, but a positive correlation with blastocyst formation rates, number of high-quality blastocysts, and pregnancy [ 170 ]. Human sperm containing higher levels of miR-34c had a 14-fold increased probability of obtaining a viable embryo [ 73 ]. Interestingly, miR-34b/c levels in sperm were only associated with a decrease in miscarriages, and increased implantation and pregnancy rates at certain Ct thresholds, determined using receiver operating characteristic curve (ROC) analysis [ 171 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Shi et al, (2020) observed a negative correlation between spermatogenic miR-34c levels and embryo developmental kinetics, but a positive correlation with blastocyst formation rates, number of high-quality blastocysts, and pregnancy [ 170 ]. Human sperm containing higher levels of miR-34c had a 14-fold increased probability of obtaining a viable embryo [ 73 ]. Interestingly, miR-34b/c levels in sperm were only associated with a decrease in miscarriages, and increased implantation and pregnancy rates at certain Ct thresholds, determined using receiver operating characteristic curve (ROC) analysis [ 171 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although sperm are mainly transcriptionally silent, a transcriptomic analysis previously conducted by our group demonstrated that exposing sperm to THC significantly changed the abundance of several fertility-associated miRs, including miR-346, miR-324, and miR-33b [22]. Mature, sperm-borne miRs are transferred to the zygote and dictate the success of embryonic development [68,73,74,76,77,[157][158][159][160][161]. Few have simultaneously evaluated cannabinoid-induced changes to fertility-associated miRs in sperm and embryos.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…The expression of miR-449b-5p is positively associated with SDF and the expression of miR-34c-5p. High expression of miR-34c-5p and miR-449b-5p in sperm increased the likelihood of retrieving viable embryos, suggesting that these two miRNAs are promising biomarkers for assessing sperm SDF and ART outcomes ( 137 ). Paternal miR-34c is believed to be involved in the early stages of embryonic development.…”
Section: Potential Of Mirnas As Biomarkers For Disease Diagnosis and ...mentioning
confidence: 99%
“…The detection of biomarkers to predict sperm quality and functional integrity has gained much interest over the last decade for human health and animal production. However, routine spermiograms have largely been unsuccessful in attaining this aim [1], though 2 of 17 techniques based on molecular approaches show promise [2][3][4]. In this regard, sperm chromatin evaluation has recently entered the set of available techniques for studying fertility as a biomarker of sperm fertility [5,6].…”
Section: Introductionmentioning
confidence: 99%